MAKNA KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI, DAN DISIPLIN KERJA DALAM PERSPEKTIF GURU TERHADAP KINERJA DI SD NEGERI KECAMATAN WALANTAKA KOTA SERANG - Nurdin Nurdin; Ahmad Mukhlis; Andriani Andriani (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
Teacher performance is the main determinant of the quality of learning in elementary schools. Up-to-date literature shows that principals' leadership, work motivation, and professional discipline contribute to the effectiveness of schools. However, most studies still position these three variables as separate constructs in quantitative approaches, so there is not much to reveal how teachers interpret leadership, motivation, and work discipline as meaning systems that shape their performance. This study aims to analyze the meaning of principals' leadership, motivation, and work discipline from a teacher